Synthesis and Structure Activity Relationship of 3-(Arylsulfonyl)-8-(piperidin-4-yl amino)quinoline Derivatives as 5-HT6 Receptor Antagonists - V.S. Nirogi, Ramakrishna; Badange, Rajeshkumar; Gudla, Parandhama; Khagga, Mukkanti (Asian Journal of Chemistry, 2014)
As part of our efforts to develop better therapies for the treatment of cognitive impairment associated with Alzheimer's disease and Schizophrenia, we have focused our research towards 5-HT6 receptor (5-HT6R) in order to identify potent and selective ligands for this purpose. Herein, we report the synthesis, structure activity relationship and biological evaluation of a novel series of 3-(arylsulfonyl)-8-(piperidin-4-yl amino)quinoline derivatives, as 5-HT6 receptor (5-HT6R) antagonists. In this work, we have shown that moving from aryl sulfonamide platform to biaryl sulfone platform retains the 5-HT6R affinity when tested in vitro in cell based reporter gene functional assay.